Effect of green tea (Camellia sinensis) extract and pre-freezing equilibration time on the post-thawing quality of ram semen cryopreserved in a soybean lecithin-based extender - Mehdipour, Mahdieh; Daghigh Kia, Hossein; Najafi, Abouzar; Vaseghi Dodaran, Hossein; García-Álvarez, Olga (Cryobiology, 2016)
The aim of this study was to determine the effect of Camellia sinensis extract as antioxidant supplement and pre-freezing equilibration times in a soybean lecithin extender for freezing ram semen. In this study, a total of 20 ejaculates were collected from four Ghezel rams and diluted with extenders (1.5% soybean lecithin, 7% glycerol) containing no supplements (control) and Camellia sinensis extract (5, 10, and 15 mg/L) and cryopreserved, immediately after thermal equilibrium was reached at 5 °C (0 h), or 4 h after equilibration. Sperm motility characteristics, membrane integrity, abnormal morphology, mitochondria activity, apoptotic status, MDA and antioxidant activities (GPx, SOD and total antioxidant capacity (TAC)) were evaluated following freeze-thawing. Camellia sinensis extract at level 10 mg/L led to the highest total and progressive motilities percentages, in comparison to other treatments (P < 0.05). Our results showed that Camellia sinensis extract at level of 5 and 10 mg/L led to higher plasma membrane integrity, mitochondria activity and Total antioxidant capacity (TAC) in comparison to the level of 15 mg/L and control group (P < 0.05). Camellia sinensis extract at 10 mg/L level produced the highest percentage of live spermatozoa and the lowest apoptotic spermatozoa in comparison to all treatments (P < 0.05). In addition, level of MDA formation significantly decreased at this concentration, 10 mg/L, compared to all treatments (P < 0.05). No differences (P > 0.05) were observed between equilibration times (0 h vs. 4 h) for sperm samples incubated with or without different concentrations of Camellia sinensis extract. In conclusion, addition of Camellia sinensis extract at level of 10 mg/L can improve post-thawing quality of ram semen cryopreserved in a soybean lecithin extender. However, further research is needed to standardize the process of Camellia sinensis extraction and specially for identifying which compounds are responsible of its beneficial effect on ram sperm cryopreservation.
Keywords: Animals; Cryopreservation; Antioxidants; Glycine max; spermie; čaj; Lecithins; Semen; Spermatozoa; rostlinné extrakty; Glycerol; ovce; Freezing; Cryoprotective Agents; Semen Preservation; Tea; Camellia sinensis extract; motilita spermií; sperma; kryoprezervace; Equilibration time; Male; Sheep; Soybean lecithin; antioxidancia; Plant Extracts; glycerol; čajovník čínský; Sperm Motility; zvířata; zmrazování; mužské pohlaví; kryoprotektivní látky; Camellia sinensis; lecitiny; uchování spermatu